JENIS AGROFORESTRI DAN ORIENTASI PEMANFAATAN LAHAN DI DESA SIMORO KECAMATAN GUMBASA KABUPATEN SIGI - Amin, Muhammad; Rachman, Imran; Ramlah, Sitti (Universitas Tadulako, 2016)
Agroforestry practices in fact has long been practiced by rural communities (local traditional agroforestry), and even in some places the implementation of agroforestry has an important role in the socio-cultural aspects of the local community. Study of the characteristics of land use (systems and pattern of agroforestry-based land use), as well as the orientation of land use is still rarely studied. Even it is not a study based agroforestry landscape, but the micro-scale (plot-based interaction). So there is no information that can explain characteristis of agroforestry landscape of the community. It is important to look at the specific characteristics of agroforestry-based land use that is owned by the community. The purpose of this study was to determine the pattern of agroforestry on community land in the Simoro village and assess the orientation of agroforestry land use community-owned Simoro village. Analysis of data used in this research are descriptive analysis and analysis of the NEP (New Environmental Paradigm). Research resulted, the pattern of agroforestry and land use at Simoro village include simple and complex agroforestry system, where the farmers combine seasonal crops and tree crops, whereas in complex agroforestry system using mix cropping pattern at home garden. The results of analysis of the NEP (New Erwironmental Paradigm) shows the value of egoistic respondents fall into the low category. This indicates that respondents, in general, have a desire to clear land to not only put the interests of the individual and the consideration of the benefit and loss agroforestry practic, but also considering into account the conservation of nature, while the value of altruristic fall in the low category. This indicates that respondents generally lack aware of the public community interest and the value of biospheric of respondents were also may be categorized of high. This indicates that the community ofÂ Simoro village generally have the awareness of the importance of environmental aspects, not only for their personal important, but also for the other village community.Keywords: Agroforestry, land uses, biospheric, alturistic, egoistic.